Phenotypic Detection and Risk Factors of Bacteria Aetiological Agents of Dental Caries in Patients in Uyo Nigeria - Onwuezobe, Ifeanyi Abraham; Udoh, Mary Athanasius; Ekuma, Agantem Emmanuel; Takon, Mary Bondick; Ngwu, Faith Amarachi (African Journal of Medicine, Surgery and Public Health Research, 2025)
Background. Dental caries is a highly prevalent oral disease that affects approximately 100% of individuals in the society. This disease causes severe damage to the teeth. Several acidophilic bacteria are implicated in the disease. This research was done to detect bacterial agents and risk factors implicated in caries in Uyo, Nigeria. Methods. A total of 120 dental plaque samples were cultured. Vitek 2 System (bioMe´rieux) was used for biochemical characterization and antibiotic susceptibility of isolates. Results. Several bacterial species (Thirteen) were obtained from significant culture growth of 27 (22.5%). Burkholderia cepacia group were 7(5.8%), and the most prevalent. Enterococcus faecalis 1(0.8%), Enterococcus spp (non E. faecalis) 1(0.8%), Pediococcus pentosaceus 1(0.8%), Kocuria kristinae 1(0.8%), Serratia ficaria 2(1.7%), Klebsiella pneumoniae 1(0.8%), Acinetobacter spp 1(0.8%) and Enterobacter cloacae ssp dissolvens 1(0.8%) were the least prevalent isolates. This study showed new bacteria species being implicated in caries, and high consumption of sugary foods being the main risk factor of caries. Conclusions. The identification of novel bacteria species in caries, and the attribution of staple foods as the lead risk factor of caries amongst dental caries patients in Uyo is a cause for alarm, as most of these people rely on carbohydrates for their daily food, as the soil of their farmlands are most favourable in yielding carbohydrate crops compared to other crops. Hence, there is need for frequent health enlightenment program, especially in the urban areas on adverse effect of frequent snacking and/or eating carbohydrates without rinsing the mouth frequently to rid it of food debris.